Combined Effect of Neem and Inert Material with Grain Protectant Against Pulse Beetle, Callosobruchus chinensis L. in Stored Green Gram - Sundria, Man Mohan; Kumar, Ashok; Srivastava, Chitra; Srivastava, Akhil Kumar (Annals of Arid Zone, 2016)
Investigations were conducted on quantitative and qualitative losses caused by pulse beetle in stored green gram and also explore the possibility of using neem, inert materials and grain protectants in combination to protect the green gram grains. The seed damage, weight loss and germination loss in green gram caused by Callosobruchlls chinensis after four months of storage were 100, 48.57 and 100%, respectively. The combination of deltamethrin (2.8 EC) at 20 mg m-2 + neem seed kernel powder (NSKP) at 15 g kg-1 seed treatment and malathion (50 EC) at 250 mg m-2 + NSKP at 15 g kg-1 seed gave 100% protection up to 12 months of storage. Whereas, deltamethrin at 20 mg m-2 + NSKP at 10 g kg-1 and malathion at 250 mg m-2 + NSKP at 10 g kg-1 seed provided full protection only up to six months. Green gram seeds treated with all doses of NSKP gave better protection over control and semi-control against the beetle. The weight loss after 12 months of storage was maximum in seeds treated with ash and minimum in seeds treated with NSKP 15 g kg-1 seed. Key words: Callosobruchlls chinensis, green gram, grain protectant, NSKP.